Power analytics of power data - Chew, Jia Yong (2014)
The world has been working hard on technology to achieve the goal in order to reduce energy consumption. The widely used method of achieving that is making use of sensors to analyze and monitor the power consumption of electrical devices in a unit or building. However, although sensors are cheap, the maintenance and configuration tends to be tough and complicated. This project is to study on how electrical appliance can be identified through power consumption signal, by decomposing the signal into different phases.